De Mammona iniquitatis. Spiritually poor: the Sturzian roots of the Encyclical “Caritas in veritate” of Benedict XVI (Stato, Chiese e pluralismo confessionale, 2012)
The present work has been done for the scope of Study in honor of Professor Franco Bolognini.SUMMARY: The spirit of the present contribution: “the economics as if the person would count1” – 1. Essential notes on the “popular capitalism” in the thought of Luigi Sturzo - 2. The economical liberty and the rules’ liberalism – 3. Synthesis considerations.